Studies in Early Hadith Literature (and the History of its Codification) together with a Critical Edition of Some Early Texts - Hamidullah, M (Journal of Malaysian and Comparative Law, 2018)
Studies in Early Hadith Literature (and the History of its Codification) together with a Critical Edition of Some Early Texts